"CYCLIST ON THE MARSH": LESSONS AND PROSPECTS OF THE LAST EU ENLARGEMENT - A. I. Tevdoy-Bourmouli (Vestnik MGIMO-Universiteta)
The latest cycle of the European Union enlargement generated a panoply of problems unknown of in the anamnesis of this organisation. Specific historic experience of the applicants pre-determined a considerable specialty of west-European fashioned democratic regimes in those countries, weakness of consensus and tolerance culture which has already rooted itself in the West-European society, and which has to a considerable degree secured stable development of Western Europe over the last decades. This constellation resulted particularly in the renaissance on the level of European establishment of the nationalist phobia and memories deeply buried decades ago. Though the scale of the eventual problems was evident to the EU leaders long before the official entry of Central and East-European (CEE) countries to the European Union, it neither blocked the admission of new members nor entailed a refusal to pursue the plans of further enlargement at the time when Brussels’ fears have panned out. The paradox is predetermined by the combination of the EU motives – common interests of the integration group with the interests both of individual members and outside actors.